Men,Women, and the Ballot – Woman Suffrage in the United States - Sebastian Braun; Michael Kvasnicka (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
Woman suffrage led to the greatest enfranchisement in the history of the United States. Before World War I, however, suffrage states remained almost exclusively confined to the American West. The reasons for this pioneering role of the West are still unclear. Studying the timing of woman suffrage adoption at state level, we find that states in which women were scarce (the West) enfranchised their women much earlier than states in which the sex ratio was more balanced (the rest of the country). High sex ratios in the West, that is high ratios of grantors to grantees, reduced the political costs and risks to male electorates and legislators of extending the franchise. They are also likely to have enhanced female bargaining power and may have made woman suffrage more attractive in the eyes of western legislators that sought to attract more women to their states. Our finding of a reduced-form inverse relationship between the relative size of a group and its success in securing the ballot may be of use also for the study of other franchise extensions and for inquieries into the dynamics of political power sharing more generally.
Keywords: D72; J16; K10; N41; N42; 330; Woman suffrage; democratization; political economy; sex ratio; Wahlrecht; Frauen; Demokratisierung; USA